Prenatal inflammation as a link between placental expression signature of tryptophan metabolism and preterm birth - Karahoda, Rona; Robles, Morgane; Marushka, Julia; Stranik, Jaroslav; Abad, Cilia; Horackova, Hana; Tebbens, Jurjen Duintjer; Vaillancourt, Cathy; Kacerovsky, Marian; Staud, Frantisek (Human molecular genetics, 2021)
Spontaneous preterm birth is a serious medical condition responsible for substantial perinatal morbidity and mortality. Its phenotypic characteristics, preterm labor with intact membranes (PTL) and preterm premature rupture of the membranes (PPROM), are associated with significantly increased risks of neurological and behavioral alterations in childhood and later life. Recognizing the inflammatory milieu associated with PTL and PPROM, here, we examined expression signatures of placental tryptophan metabolism, an important pathway in prenatal brain development and immunotolerance. The study was performed in a well-characterized clinical cohort of healthy term pregnancies (n = 39) and 167 preterm deliveries (PTL, n = 38 and PPROM, n = 129). Within the preterm group, we then investigated potential mechanistic links between differential placental tryptophan pathway expression, preterm birth and both intra-amniotic markers (such as amniotic fluid interleukin-6) and maternal inflammatory markers (such as maternal serum C-reactive protein and white blood cell count). We show that preterm birth is associated with significant changes in placental tryptophan metabolism. Multifactorial analysis revealed similarities in expression patterns associated with multiple phenotypes of preterm delivery. Subsequent correlation computations and mediation analyses identified links between intra-amniotic and maternal inflammatory markers and placental serotonin and kynurenine pathways of tryptophan catabolism. Collectively, the findings suggest that a hostile inflammatory environment associated with preterm delivery underlies the mechanisms affecting placental endocrine/transport functions and may contribute to disruption of developmental programming of the fetal brain.
Keywords: Gene Expression Regulation; tryptofan; transkriptom; biologické markery; Inflammation; Risk Factors; Biomarkers; výpočetní biologie; předčasný porod; Pregnancy; těhotenství; Transcriptome; Placenta; výsledek těhotenství; Disease Susceptibility; Premature Birth; Tryptophan; stanovení celkové genové exprese; Gene Expression Profiling; zánět; placenta; Pregnancy Outcome; lidé; ženské pohlaví; Humans; regulace genové exprese; metabolické sítě a dráhy; rizikové faktory; náchylnost k nemoci; Female; Metabolic Networks and Pathways; Computational Biology